2014
DOI: 10.1128/jvi.02681-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Potential Permissive Neuraminidase Mutations on Viral Fitness of the H275Y Oseltamivir-Resistant Influenza A(H1N1)pdm09 VirusIn Vitro, in Mice and in Ferrets

Abstract: , and H275Y/V241I/N369K (a natural variant) NA mutants were generated by reverse genetics. Replication kinetics were performed by using ST6GalI-MDCK cells. Virulence was assessed in C57BL/6 mice, and contact transmission was evaluated in ferrets. The H275Y mutation significantly reduced viral titers during the first 12 to 36 h postinfection (p.i.) in vitro. Nevertheless, the WT and H275Y viruses induced comparable mortality rates, weight loss, and lung titers in mice. The T289M mutation eliminated the detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…However, the proportion of the early mutant A/Chiba/1017/2009 to that of wild-type virus decreased significantly, whereas the proportion of the mutant A/Sapporo/114/2013 from the cluster to that of wildtype virus was 84% at passage 1, decreasing to 69% and 39% at passages 2 and 3, respectively, indicating that the mutant A/Sapporo/114/2013 virus continued to replicate efficiently, competing with the wild-type virus at the initial cycle of infection. These results suggest that the Sapporo/Hokkaido cluster virus retained the ability to grow comparably to the wild-type virus and grew significantly better than did the early mutant virus, consistent with previous reports (13,14).…”
Section: Transmissibility Of the H275y Mutant Virus In Ferretssupporting
confidence: 91%
See 4 more Smart Citations
“…However, the proportion of the early mutant A/Chiba/1017/2009 to that of wild-type virus decreased significantly, whereas the proportion of the mutant A/Sapporo/114/2013 from the cluster to that of wildtype virus was 84% at passage 1, decreasing to 69% and 39% at passages 2 and 3, respectively, indicating that the mutant A/Sapporo/114/2013 virus continued to replicate efficiently, competing with the wild-type virus at the initial cycle of infection. These results suggest that the Sapporo/Hokkaido cluster virus retained the ability to grow comparably to the wild-type virus and grew significantly better than did the early mutant virus, consistent with previous reports (13,14).…”
Section: Transmissibility Of the H275y Mutant Virus In Ferretssupporting
confidence: 91%
“…Previous reports suggested that the introduction of the V241I and N369K substitutions to the NA protein of the H275Y mutant A(H1N1)pdm09 virus resulted in greater viral fitness (13,14). Because all circulating viruses in Japan, including the cluster viruses, possessed the V241I and N369K substitutions (Table 1 and (Fig.…”
Section: Transmissibility Of the H275y Mutant Virus In Ferretsmentioning
confidence: 96%
See 3 more Smart Citations